Identificação e caracterização molecular do vírus da doença infecciosa da bolsa cloacal em um lote de frangos de corte em Buriti Alegre, GO - Brasil, no ano de 2001 - Paula, Márcia Beatriz Cardoso de (2003)
In order to identify and characterize the causative agent of a suggestive clinicai case of infectious bursal disease (IBD) that affected a 34-day-old commercial broiler chickens flock in Buriti Alegre (Goias State, Midwestern Brazil), in the year 2001 we carried out a combination of classic and modern virological methods. Histopathological analysis of the bursa revealed necrosis, presence of depleted follicles, and some infiltration of heterophils, edema and formation of cystic cavities that are the compatible lesions observed in IBD. Inoculation of embryonated eggs of specific-pathogen-free (SPF) chickens with macerated bursa suspension resulted in embryo mortality and gross lesions compatible with that caused by IBDV. Samples of bursa were submitted to a nested reverse transcriptase-polymerase chain reaction (RT-PCR) procedure with IBDV specific primers. This reaction amplified a fragment with expected size, which was digested with restriction enzymes and revealed a restriction fragment length polymorphism (RFLP) pattern that did not match any of the 17 RFLP patterns described previously (Ikuta et al., 2001). All these results indicated that the isolated etiological agent was the IBDV and the molecular method was essential to obtain a conclusive laboratorial diagnostic of the disease. In this study, the presence of gross and microscopical lesions in bursa is an indication that the disease that occurred in the commercial broiler chicken flock was caused by the IBDV. The detection of a new RFLP pattern indicated that this agent is a new isolate.